A Framework for Knowledge-Driven Customer Relationship Management - Goon, Tuck Choy (2005)
Customer Relationship Management (CRM) initiatives are increasingly recognised as a major tool to maintain or even to compete with other organisations worldwide. The competitive benefits of CRM efforts have been widely published by researchers and consulting firms. This study look at Customer Relationship Management, CRM system and how background knowledge of an industry can guide the discovery process through means of data mining techniques and incorporate discovered patterns to retain existing customers and at the same time pinpoint accurately to new sales. In this study, we will examine the issues surrounding the convergence of KDD (Knowledge Discovery in databases) and CRM in building knowledge -driven CRM (K-CRM). By understanding the issues and challenges, we hope to achieve better customer understanding and thus, create a better CRM solution. In this study, we also demise a framework for implementing K-CRM initiatives so that, future implementations of K-CRM can be more successful and the development time can be shortened.